Uma Abordagem para Sensoriamento Urbano Preliminar Usando Coletores de Dados - Resende, Ítalo Raphael Amador (2016)
This study suggests the use of a approach to initial urban sensing, in the context of intelligent cities, by data collectors. The approaches currently used for the instrumentation of the cities are usually based on fixed sensors and present challenges relating to power-up, security, maintenance and communication of the sensors, resulting on the increase of the project’s cost. In order to decrease the complexity and costs observed in current models, we propose the use of existing mobility agents (such as metropolitan buses, for example) to provide mobility to traditional sensors. We believe this strategy can help overcome some of the existing challenges and allow a preliminary sensing of the cities in a more affordably way. To evaluate the feasibility of the proposed approach, a series of experiments were conducted using climate microstations positioned statically and also in motion. One of the evaluation fronts was to compare the change in average physical quantities obtained through frequent readings versus more sporadic readings that were collected by stationary sensors. Then the results obtained were compared with samples collected in a mobile way with the use of mobile agents equipped with sensors acting as urban data collectors. The results indicate that the approach is very promising and may be used in combination with conventional approaches, such as the initial detection of heat islands, pollution or traffic jam which can subsequently be monitored with equipments of greater precision.